Risks, Patterns, and Preventive Measures in the Analysis of Snowboarding Injuries - Kotowicz, Zuzanna; Pabiś, Jakub; Podgórski, Piotr; Górecka, Sandra; Olszański, Miłosz; Bogusz, Aleksander; Kwiatkowski, Oskar; Kołodziej, Anna; Król, Anita (Journal of Education, Health and Sport, 2024)
Introduction Snowboarding is an activity that appears to be gaining popularity among people who are interested in winter sports. The dynamic evolution of the method of snowboarding comes with it the risk of injuries, the consequences of which can be catastrophic. As a result of the fact that this sporting activity is distinguished by a diverse riding technique and calls for the use of specialized equipment, the mechanism of damage is also distinct from that which is known in, for instance, skiing. In addition, comparable to skiing, snowboarding has a sub-discipline that is linked with the execution of tricks and jumps. In a disproportionate manner, this raises the probability of an accident occurring. Wrist, shoulder, and ankle joints are among the most often injured structures in the body. Trauma to the brain and spine are remarkably uncommon, nonetheless, they are the ones that have the most serious repercussions. It is imperative that special attention be made to the avoidance of these incidents, which is why both medical professionals and proprietors of ski resorts stress the need of people wearing helmets and other protective gear, such as wrist guards. It is anticipated that the implementation of these techniques will lead to a decrease in the occurrence of the most common and serious forms of injuries, as well as a reduction in the strain placed on the organization that provides medical care. Aim of the study This review aims to characterize the most common injuries acquired during snowboarding, analyze their mechanism and to show methods of prevention. Material and method This article presents the current state of knowledge on snowboarding injuries, their mechanisms and prevention in various scientific articles. Publications describing injuries that occur while snowboarding were reviewed using the PubMed platform. The search included the keywords 'snowboard', 'injuries', 'fracture', ‘trauma’.